Translation and cultural validation of the University of Washington Caregiver Stress and Benefit Scales - Dagmar Amtmann; Alyssa M. Bamer; Rana Salem; Arnold R. Gammaitoni; Bradley S. Galer; Mark P. Jensen (Journal of Patient-Reported Outcomes, 2021)
Abstract Background English versions of the University of Washington Caregiver Stress (UW-CSS) and Benefit (UW-CBS) Scales were developed in the United States (US) to measure impact on caregivers of caring for a child/children. Caregiving stress and benefit are important constructs to study worldwide. The purpose of this study was to translate and validate the UW-CSS and UW-CBS into French, German, Italian, and Spanish languages. Method UW-CSS and UW-CBS were translated using forward and backward translation with reconciliation. Cognitive interviews (CIs) were completed with caregivers of children < 18 years with severe epilepsy. Translated versions were also administered to at least 100 caregivers in each of the four countries: France, Germany, Italy, and Spain. Differential item functioning (DIF) analyses were used to assess linguistic and cultural bias by country. The US development sample of 722 caregivers was used as a comparison sample for DIF analyses. DIF adjusted scores were calculated to determine impact of DIF on the item response theory (IRT)-based T-score. Benefit and stress scores were also calculated and compared across countries and health condition subgroups. Finally, short forms were modified to minimize the impact of DIF on the UW-CSS and UW-CBS T-scores and to reflect feedback from CIs. Results Interviews were completed with 47 caregivers (German n = 14; Spanish n = 10; French n = 13; Italian n = 10). UW-CSS and UW-CBS were administered to 456 (German n = 117, Spanish n = 114, French n = 115, Italian n = 110) caregivers of children with and without health conditions. All stress items functioned well in CIs, though results indicated statistically significant DIF for three items in multiple countries and in the overall sample. Four of the 13 benefit items were problematic based on CI feedback, and six items showed DIF in one or more countries or in the combined sample. However, average differences between DIF adjusted and non-adjusted scores were minimal for both scales and all comparisons, indicating the impact of DIF on the total score was negligible. Conclusion Modified short forms functioned well in all four of the translated versions. All language versions are freely publicly available.